Biomarkers and heterogeneous fibroblast phenotype associated with incisional hernia - Thankam, Finosh G.; Larsen, Nicholas K.; Varghese, Ann; Bui, Thao-Nguyen; Reilly, Matthew; Fitzgibbons, Robert J.; Agrawal, Devendra K. (Molecular and cellular biochemistry, 2021)
Development of incisional hernia (IH) is multifactorial but inflammation and abdominal wall ECM (extracellular matrix) disorganization are key pathological events. We investigated if the differential expression of fibroblast biomarkers reflects the cellular milieu and the dysregulated ECM in IH tissues. Expression of fibroblast biomarkers, including connective tissue growth factor, alpha-smooth muscle actin (α-SMA), CD34 (cluster of differentiation 34), cadherin-11 and fibroblast specific protein 1 (FSP1), was examined by histology and immunofluorescence in the hernial-fascial ring/neck tissue (HRT) and hernia sack tissue (HST) harvested from the patients undergoing hernia surgery and compared with normal fascia (FT) and peritoneum (PT) harvested from brain-dead healthy subjects undergoing organ procurement for transplantation. The H&E staining revealed alterations in tissue architecture, fibroblast morphology, and ECM organization in the IH tissues compared to control. The biomarker for undifferentiated fibroblasts, CD34, was significantly higher in HST and decreased in HRT than the respective FT and PT controls. Also, the findings revealed an increased level of CTGF (connective tissue growth factor) with decrease in α-SMA in both HRT and HST compared to the controls. In addition, an increased level of FSP1 (fibroblast specific protein 1) and cadherin-11 in HRT with decreased level in HST were observed relative to the respective controls (FT and PT). Hence, these findings support the heterogeneity of fibroblast population at the laparotomy site that could contribute to the development of IH. Understanding the mechanisms causing the phenotype switch of these fibroblasts would open novel strategies to prevent the development of IH following laparotomy.